Clinical Characterization of Serum Docosahexaenoic Acid and Its Relationship With Inflammation Factors in Patients With Diabetic Nephropathy (Iranian Journal of Kidney Diseases, 2018)
Introduction. A variety of molecular pathways, such as generation of advanced glycation end products, inflammation, and oxidative stress, are involved in the development of diabetic nephropathy (DN). Recently, a protective effect of omega-3 polyunsaturated fatty acids on the kidney has been reported. This study aimed to determine serum docosahexaenoic acid (DHA) level and its association with inflammation factors in patients with DN. Materials and Methods. One hundred patients with type 2 diabetic mellitus were divided into 3 groups of non-DN, early DN, and clinical DN, based on 24-hour urinary albumin levels. Hemoglobin A1c, biochemical indicators, β2-microglobulin, and 24-hour urine albumin levels were assessed. Enzyme linked immunosorbent assay was applied to determine the serum concentrations of DHA, advanced glycation end products, fractalkine, superoxide dismutase, and tumor necrosis factor-α. Results. Lower serum DHA and superoxide dismutase and higher serum β2-microglobulin and 24-hour urine albumin levels were associated with clinical DN, compared to no DN and early DN. The reductions in serum DHA levels were different among the patients with early and clinical DN, stratified by sex, body mass index, and serum lipid levels. Serum DHA significantly correlated positively with superoxide dismutase and negatively with fractalkine and tumor necrosis factor-α in the patients with DN. Conclusions. Docosahexaenoic acid may suppress the expression and secretion of fractalkine through inhibiting the tumor necrosis factor-α signaling pathway in DN patients, which improves inflammation and oxidative stress of the kidney, and in turn, delaying the development of DN.